A contribution to the theory of the trade cycle - Hicks, John R. (Oxford : Clarendon Press, 1950)
This book presents an economic model that shows a cyclical movement in output. Consumption in each period is a function of the level of income in some earlier period (or periods). Investment consists of autonomous investment, which is independent of output, and of induced investment, which is a function of the increase in output in some earlier period (or periods).
Includes index.
lje 03/10/2018
Loans
Keywords: Business cycles